Research on Unstable Heating Test of Multi-Split Air-condition (Heat Pump) Unit - Shi Min; Zhong Yu; Zhang Xiuping (Zhileng xuebao)
Seasonal performance evaluation index is taken as the direction to evaluate multi-split air-condition (heat pump) units (Hereinafter referred to as: VRF) in the future. The challenge on unstable heating performance test for VRF unit is discussed when seasonal performance evaluation index is used. Advantages and disadvantages of unstable heating performance test methods in relevant standards are analyzed. The conclusion indicates that the unstable heating performance test methods in EN and ISO standards reflect the heating performance of VRF units more objectively, and are with good operability and repeatability. Potential effect of the unstable heating performance test method in EN and ISO standards on the development of VRF in China is investigated. The outline and issues of Chinese unstable heating performance test method for VRF units are suggested.